التخطيط العمراني والوقاية من الجريمة - دلالة, ليليان (Latakia University Journal -Engineering Sciences Series, 2019)
"كما تكوّنون المدينة تكوّنكم" عبارة تصف دور المسكن والحي في تحديد مستوى السلوك الاجتماعي لدى تجمع المدن. وهناك أساليب تخطيطية وتصميمية للمناطق السكنية تلعب دوراً مهماً ووثيقاً في موضوع الجريمة. ولا بدَّ أن يحتل تحقيق الأمن، وهدوء البيئة الاجتماعية في المدينة، حيزاً مهماً في أعمال، تحضيرات، وممارسات تخطيط المدينة، أو في إعادة تخطيطها وبنائها. وذلك لأن التخطيط، هو جزء من برنامج اجتماعي أوسع، يعتبر المسؤول المباشر عن توفير القاعدة المادية لحياة اجتماعية أفضل. ولكن مع الأسف الشديد إن معظم البحوث التي عالجت ظاهرة الجريمة والأمن اقتصرت على دراسة الجوانب الاجتماعية، الاقتصادية، المادية والسياسية لها، ولم تولي جوانب التخطيط العمراني الاهتمام الكافي. يبين البحث أهمية مناقشة جوانب التخطيط العمراني المؤثرة في رفع مستوى الأمن بالأحياء السكنية، وقد تساعد نتائجه في معرفة طبيعة المشاكل الأمنية الناجمة عن التخطيط، وإجراء الكثير من التعديلات الإيجابية على القائم من الأحياء السكنية المعاصرة في المدن." As form the city that forms you ", a phrase describes the role of house and district in defining the social behavior level at the gathering of cities. there are planning and design styles of the residential regions that have an important role in the crime topic. We must occupy the achievement of security and calm social environment in the city, an important aspect in the work, preparation, and practice of city planning, or in the re-planning and construction. This is because the planning, is part of a broader social program, which is directly responsible for the provision of social material base for a better life. but unfortunately most of the researches that treated the phenomenon of crime and security studied social, economic, material, and political sides only, And it did not give the construction planning sides enough care. This research shows the importance of discussing Many sides of urban planning that affect increasing the level of security in residential neighborhoods. And its results may help in knowing the nature of safety problems that appears because of planning, and in doing many positive modifiers in existing contemporary residential neighborhoods in cities.